Low-latitude climate change linked to high-latitude glaciation during the late paleozoic ice age: Evidence from terrigenous detrital kaolinite - Zhang, Peixin; Yang, Minfang; Lu, Jing; Shao, Longyi; Wang, Ziwei; Hilton, Jason (Frontiers in Earth Science, 2022)
The Late Paleozoic Ice Age (LPIA; ca. 335–260 million years ago) was one of the most significant glacial events in Earth’s history. It records cycles of ice advance and retreat in southern high-latitude Gondwana and provides a deep-time perspective for climate-glaciation coevolution. However, climate records using clay mineral proxies from the LIPA are poorly developed in low latitudes, particularly in the North China Plate (NCP) on the eastern Paleo-Tethys. We address this through a detailed mineralogical study of the marine-continental sedimentary succession in the Yuzhou Coalfield from the southern NCP. We apply biostratigraphy and high-resolution clay mineral composition to reconstruct the latest Carboniferous to early Permian chronostratigraphy and climate change. The Benxi, Taiyuan, and Shanxi formations in the study area are assigned to the Gzhelian, Asselian-Artinskian, and Kungurian-Roadian stages respectively, and the Carboniferous and Permian lithostratigraphic units across the NCP recognized as widely diachronous. Under scanning electron microscopy, detrital micromorphology of kaolinite is mostly as irregular fragments with sizes of 1–5 m. Illite crystallization varies from 0.22 to 1.88 ∆°/2θ (x̄ = 0.49 ∆°/2θ) and indicates changes in kaolinite content to be a robust proxy for paleoclimate reconstruction. Kaolinite data show alternating warm-humid and cool-humid climate conditions that are roughly consistent with the calibrated glaciations and nonglacial interval successions recognized in high-latitude Gondwana. These include the Asselian-early Sakmarian and late Sakmarian-early Artinskian glacials, as well as the climatic transition to glacial P3 during the Roadian. Our results indicate a comparatively cool-humid and warm-humid climate mode in low-latitude NCP during glacial and nonglacial periods respectively. This is a significant step toward connecting climate change in low-latitudes to high-latitude glaciation during the LPIA in eastern Paleo-Tethys.